2006
DOI: 10.1080/14786430600801443
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of {111} planar defects induced in silicon by hydrogen plasma treatments

Abstract: Microstructural characterization by transmission electron microscopy of the {111} planar defects induced in Si by treatment in hydrogen plasma is discussed. The {111} defects are analyzed by conventional (TEM) and high-resolution transmission electron microscopy (HRTEM). Quantitative image processing by the geometrical phase method is applied to the experimental high-resolution image of an edge-on oriented {111} defect to measure the local displacements and strain field around it. Using these data, a structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Thus, one can expect that hydrogen may form precipitates and introduce structural defects. [11][12][13][14][17][18][19][20] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one can expect that hydrogen may form precipitates and introduce structural defects. [11][12][13][14][17][18][19][20] …”
Section: Methodsmentioning
confidence: 99%
“…11,[17][18][19][20] While many studies have focused on platelet formation in n-and p-type monocrystalline Si, very few have studied the influence of extended defects such as dislocations, stacking faults, and twins on hydrogen induced defect formation in mc silicon. Even fewer, if any, have studied hydrogen plasma treated, as-cut, mc material.…”
Section: Transmission Electron Microscopy Study Of Hydrogen Defect Fomentioning
confidence: 99%
“…[18][19][20][21] We have demonstrated that in certain experimental conditions, the surface roughness can be reduced down to 1-2 nm, while a plasma treatment at low power (50-100 W) results in inducing a high density of structural defects confined to a narrow band (30-50 nm) of Si adjacent to the treated surface. We have found and characterized three main types of induced defects, such as {111} planar defects, {001} planar defects, and nanocavities.…”
Section: Introductionmentioning
confidence: 90%
“…18 Once created, single vacancies diffuse inside the Si wafer even at room temperature. It has been shown 13,30 that hydrogen implantation followed by thermal annealing leads to the nucleation and growth of hydrogen related cavities.…”
Section: Laser Annealingmentioning
confidence: 99%
“…[35][36][37] One advantage of this method is that it also can texture ͕111͖ silicon and, therefore, has potential for texturing mc Si. 35 This is in contrast to pure hydrogen plasma treatments, [38][39][40][41][42][43][44][45][46][47][48] where texturing depends on grain orientation and hydrogen induced structural defects form in the bulk. [38][39][40][41][42][43][44][45][46][47][48] In the tungsten hot filament case, the high temperature, ϳ800°C ͑in contrast to ϳ250°C for H-plasma treatments [43][44][45][46][47] ͒, prevents hydrogen defect formation in the bulk.…”
Section: Introductionmentioning
confidence: 99%